Toward a code for the interactions of zinc fingers with DNA: selection of randomized fingers displayed on phage. - Choo, Y (1994)
We have used two selection techniques to study sequence-specific DNA recognition by the zinc finger, a small, modular DNA-binding minidomain. We have chosen zinc fingers because they bind as independent modules and so can be linked together in a peptide designed to bind a predetermined DNA site. In this paper, we describe how a library of zinc fingers displayed on the surface of bacteriophage enables selection of fingers capable of binding to given DNA triplets. The amino acid sequences of selected fingers which bind the same triplet are compared to examine how sequence-specific DNA recognition occurs. Our results can be rationalized in terms of coded interactions between zinc fingers and DNA, involving base contacts from a few alpha-helical positions. In the paper following this one, we describe a complementary technique which confirms the identity of amino acids capable of DNA sequence discrimination from these positions.